"CHRYSIN" AMELIORATES CARDIAC HYPERTROPHY IN RATS. (April 2021) - Sahu, Anil Kumar; Meshram, Sonali; Arya, D.S.
Abstract: Objective: Cardiac hypertrophy: thickening of cardiac muscle which causes decreased pumping ability of heart, results in cardiac dysfunction. Chrysin, is a naturally occurring flavone, found in bee propolis and honey and possesses anti-oxidant, anti-inflammatory, anti-diabetic, anti-estrogenic, anti-tumour and anti-apoptotic properties. Present study investigates the effect of Chrysin on isoproterenol induced cardiac hypertrophy in male albino wistar rats. Design and method: Male wistar albino rats were divided into eight groups: Group 1 (Control); Group 2 (Isoprotorenol); Group 3; 4; 5 and 6 (Chrysin 15, 30, and 60 mg/kg and 60 mg/kg per se p.o. respectively), Group 7 (Losartan 10 mg/kg; p.o.) and Group 8 (Losartan 10 mg/kg; p.o. + Chrysin 60 mg/kg; p.o.) in which respective compound was given accordingly. ISO (3 mg/ kg; s.c.) was administered daily for 28 days to all groups except normal and per se to induce Cardiac Hypertrophy. On day 29, animals were anesthetized, blood was taken from heart and serum was separated for estimation of cardiac injury parameters and inflammatory cytokines level. Thereafter, rats were sacrificed and heart was isolated and preserved for biochemical, histopathological, ultra-structural, immuno-histochemical and western blot analysis. Results: Chrysin with Losartan treatment of 28 days significantly attenuated cardiac hypertrophy via. decreased cardiac injury markers, inflammatory cytokine, oxidative stress and apoptosis. The combination of Chrysin and Losartan exhibited significant effect to that of Chrysin or Losartan separately. The histopathological, Immunhistochemical and immunoblot analysis showed that the chrysin attenuates cardiac hypertrophy via modulation in MAPK pathways and showing anti-apoptotic effect. The combination of Chrysin and Losartan showed beneficial effect among all groups. Conclusions: Chrysin and Losartan reduce Isoprotorenol- induced cardiac hypertrophy by mitigating oxidative stress, inflammation and apoptosis resulting in improvement of cardiac function, structural changes and antioxidants levels. Chrysin and Losartan in combination attenuated DNA damage or apoptosis and showed best cardio-protection against Cardiac hypertrophy.